The role of obesity in physiological stress, balance, and proprioception during repetitive manual material handling tasks - Sergio A. Lemus; Jaron Mohammed; Cheng-Bang Chen; Thomas M. Best; Eduard Tiozzo; Francesco Travascio (PLoS ONE, 2025)
Manual laborers often experience fatigue-related incidents, which increase their risk of balance disturbances and falls. Previous research indicates that obese individuals may reach critical fatigue levels during repetitive lifting. This study examines whether this BMI-based fatigue pattern also applies to other manual handling activities. Therefore, assessing balance impairment under high physiological stress conditions will help quantify the increased fall risk in obese individuals. Thirty participants performed carrying and pushing/pulling tasks, with weights determined using the Liberty Mutual Equations to align with NIOSH criteria. Balance tests were conducted before and after each task. A two-way ANOVA compared energy expenditure rate (EER) across BMI classifications and sex, while a mixed-effects model analyzed the effects of EER, BMI, and sex on balance and proprioception tests. Results indicated a positive correlation between BMI and EER for both carrying (p = 0.003) and pushing/pulling (p = 0.013). In the mixed-effects model, BMI (p = 0.032) and EER (p = 0.037) were positively correlated with knee proprioception loss, whereas EER was negatively correlated with balance (p = 0.020). These findings confirm that obese individuals face critical fatigue levels, as well as impaired proprioception and balance, during repetitive handling tasks.